Operational sex ratio predicts the opportunity and direction of sexual selection across animals. (16th January 2018) - Janicke, Tim; Morrow, Edward H.
Abstract: The operational sex ratio (OSR) has long been assumed to be a key ecological factor determining the opportunity and direction of sexual selection. However, recent theoretical work has challenged this view, arguing that a biased OSR does not necessarily result in greater monopolisation of mates and therefore stronger sexual selection in the mate‐limited sex. Hence, the role of the OSR for shaping animal mating systems remains a conundrum in sexual selection research. Here we took a meta‐analytic approach to test whether OSR explains interspecific variation in sexual selection metrics across a broad range of animal taxa. Our results demonstrate that the OSR predicts the opportunity for sexual selection in males and the direction of sexual selection in terms of sex differences in both the opportunity for sexual selection and the Bateman gradient (i.e. the selection differential of mating success), as predicted by classic theory.